Analisis Volatilitas Cryptocurrency, Emas, Dollar, dan Indeks Harga Saham (IHSG) - Oey Laurensia Dewi Warsito (Universitas Pendidikan Ganesha, 2020)
This research was conducted to analyze cryptocurrency volatility. Gold, Dollar Index, and Composite Stock Prices Index in the Indonesia Stock Exchange (IDX) variable are used as independent variables. The cryptocurrency objects in this study are Bitcoin and Ethereum which have the largest market capitalization. The data used in this study is from 1st January 2017 to 31st December 2019. This study uses GARCH analysis. The result of this study indicates that the volatility of Bitcoin and Ethereum is not influenced by other variables, but it is influenced by the prices of each Bitcoin and Ethereum at past prices. This shows that the cryptocurrency market is an inefficient market.